A semântica da objetividade na Ciência da Lógica - Illetterati, Luca (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: The notion of ‘objectivity’ in the Hegelian conceptual constellation is one that, if not ambiguous, is at least characterized by a strong polysemy. In this paper, I intend to linger with the significance that ‘objectivity’ assumes for Hegel in relation to logic and therefore with the question of what type of ‘objectivity’ it is that Hegel attributes to logical thought. The thesis I would like to assert is that one can understand the Hegelian notion of ‘objectivity’ only if one recognizes the inextricable bond between the epistemological and the ontological in Hegel's philosophy, or rather, only if one acknowledges the radical critique Hegel poses to the modern gap between the epistemological dimension and the ontological dimension. I will therefore to show that the Hegelian notion of ‘objectivity’ should be understood neither in traditionally epistemological terms (as a notion belonging to some ‘theory of knowledge’ or ‘epistemology’) nor in purely ontological terms (as a property exclusive to being, facts, or the states of things).